KONSEP PARENTING DALAM AL-QUR’AN (Analisis Deskriptif Penafsiran Rasyid Ridha dalam Tafsir al-Manar) - Wiwin Ainis Rohtih; Suhaelah Nahlah Aminah (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2023)
Islam is a religion that teaches its people to be able to live the life of the world and the hereafter well. Therefore, Islam provides the best way so that its people can achieve it. Islam also teaches it very universally. As explained in the Qur'an very clear and clearly. The Qur'an has also regulated everything, including the issue of educating children. This study intends to examine how Muhammad Rasyid Rida's opinion on the verses about parenting, and how the interpretation of the verses about parenting in the interpretation of Al-Manar. The purpose of this research is to determine Muhammad Rasyid Rida's opinion and interpretation of the verses about parenting in his interpretations entitled Tafsir Al-Manar. The approach used by the researchers in this study is a qualitative approach that is descriptive-analytical. The first step is to collect verses of the Qur'an related to parenting, then these verses are interpreted using a book of interpretation written by Muhammad Rasyid Ridha entitled Tafsir Al-Manar, then analyzes the interpretation of Muhammad Rasyid Rida in his interpretation book, then the author concludes into several sentences. From the results of this study indicate that the methodology of interpretation used by Muhammad Rasyid Rida is the tahlili method, where in interpreting the verses of the Qur'an, Rashid Rida used the interpretation of the Qur'an with the Qur'an, with the Prophet’s hadits, the opinions of the companions and tabi’in. Muhammad Rasyid Rida argues that both parents must agree in educating their children by giving freedom and independence of mind and understanding in science and freedom of will in the practice, so that parents will get the child to be able to manage their own affairs and choose what they think is good for themself and his community.